Invisible Labor in Work Life: The Interaction Between Identification, Work Immersion, and Stress - SOYER, Melis; GİRİŞKEN, Arzu (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study presents an empirical analysis of the complex dynamics among job stress, emotional labor, organizational identification, and job engagement. The primary objective is to examine how job stress affects the dimensions of emotional labor within the context of organizational identification and job engagement. The research is based on a published 2022 PhD dissertation. The sample consists of 400 employees from the ground services sector of the aviation industry in the Marmara Region, selected using a convenience sampling method. Data was collected through comprehensive surveys. The findings reveal statistically significant relationships between emotional labor and job stress, as well as the effects of job engagement on job stress and emotional labor. Furthermore, the results confirm the indirect influence of organizational identification and job engagement on job stress, supporting the research hypotheses. This study provides valuable insights into emotional labor, stress management, and organizational behavior within the aviation industry. It extends previous research by integrating job engagement and emotional labor into the relationship between organizational identification and job stress, offering a novel contribution to the literature on emotional labor in the aviation industry.